CHARACTERIZATION OF BIODEGRADABLE POLYURETHANE POLYMER BASED ON BENTONITE-CHITOSAN HYBRID PALM - SA, Sabiila Yasara; Syafruddin, S; Rihayat, Teuku (Jurnal Sains dan Teknologi Reaksi, 2023)
Corrosion problems that often occur cause various damages and losses. The coating process has the advantage of being able to protect the metal surface from environmental influences that result in corrosion of the metal. The innovation of combining Polyurethane with Bentonite-Chitosan filler is able to make the polymer have better corrosion resistance. This study aims to see the effect of mixing between Polyurethane and Bentonite-Chitosan filler. The sample formulation used is polyurethane with variations of bentonite and chitosan 1%, 3%, 5%, 7%, 9%. The addition of Bentonite-chitosan filler affects the mechanical properties of the material. Characterization with the addition of Bentonite and Chitosan produces a polymer that has good thermal stability and good corrosion resistance. Test result Fourier Transform Infrared(FT-IR) there are functional groups NH, CH, C=O. Based on test resultsThermogravimetric Analysis(TGA) samplePolyurethane with modified bentonite 9%/chitosan 9% w/w has the best thermal stability among other samples where the sample starts to degrade (on set) at 419.22(oC) and stops degrading (end set ) at 521.94 (oC) with a weight loss of -31.156%. Polyurethane samples with 1% bentonite/chitosan 9% w/w modification had lower thermal stability where the sample started to degrade (onset) 312.21 (oC) and stopped degrading (end set) at 391.09 (oC) with a weight loss of -55.729 %. The results of the morphological test using the SEM tool show that the chitosan chains dispersed well into the bentonite interlayer. The corrosion test showed that the addition of bentonite and chitosan affected the corrosion rate, the greater the composition of bentonite and chitosan, the lower the corrosion rates. the best sample with a ratio of Polyurethane/Bentonite/Chitosan 9:9% w/w experienced the smallest corrosion rate of 5.08mpy and a mass loss of 0.1 gram.Keywords: Biodegradable, Corrosion, Polyurethane, Bentonite, Chitosan